2012
DOI: 10.5251/abjna.2012.3.6.253.261
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mulching materials on agronomic characteristics, pests of pepper (Capsicum annuum L.) and their natural enemies population

Abstract: The trial was to study the effect of different mulching materials on agronomic characteristics, pests and their subsequent effect on the natural enemies of the pests of pepper (Capsicum annuum).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 17 publications
1
9
1
1
Order By: Relevance
“…The control (unmulch) had the lowest plant height followed by groundnut (live mulch). The effect of cowpea as life-mulch in reducing plant height has been reported by Mochiah et al (2012) in okra. This could be as result of competition for nutrient, light and space between okra and different weed types in the control and cowpea life-mulch with okra plants on the other hand.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The control (unmulch) had the lowest plant height followed by groundnut (live mulch). The effect of cowpea as life-mulch in reducing plant height has been reported by Mochiah et al (2012) in okra. This could be as result of competition for nutrient, light and space between okra and different weed types in the control and cowpea life-mulch with okra plants on the other hand.…”
Section: Discussionmentioning
confidence: 99%
“…Throughout the duration of the experiment, application of mulch had significant effect on the number of leaves of okra. In crop production, mulching is one of the most beneficial and simplest agronomic practices used to aid water retention, increase soil nutrition, improve seed germination and seedling survival, suppress weed growth, enhance pest and disease protection, enhance root establishment, transplant survival and overall plant growth performance (Mugalla et al, 1996;Chalker-Scott, 2007;Iqbal, et al, 2009;Mochiah et al, 2012). Generally, mulched plants have been shown to have higher shoot dry weight than non-mulched plants (Amoroso et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The height will increase with decrease in competition with weeds. In this connection, Mochiah et al (2012) reported an increase in plant height of pepper with mulching of the soil. The mulching of Cannabis sativa effectively reduced the weed competition which eventually helps increase the plant height as compared to weedy check.…”
Section: Potato Plant Height (Cm)mentioning
confidence: 99%